Concurso Nacional de Artistas Jóvenes en el panorama artístico de Arequipa, CCPNAA (1986-2012) - Mamani Quilcca, Gabriela Giovanna (2025)
This article analyzes the relevance of the National Young Artists Contest in the panorama of Arequipa painting scene between 1986 and 2012. First, a brief history of Arequipa´s art is offered, addressing the panorama and the contests that existed, then the history of the contest is reviewed, its origins, highlights, artistic and social relevance and also its impact within the field of local painting. Later, some painters who acquired recognition and significance by occupying the first positions in said event are mentioned. A brief analysis and assessment of the most relevant works and aesthetic characteristics of their authors is outlined. Finally, the variety of sources of information and research such as books, journalistic articles, theses, catalogs and interviews are mentioned.